2021
DOI: 10.1002/qj.4138
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of kilometre and sub‐kilometre scale simulations of a foehn wind event over the Larsen C Ice Shelf, Antarctic Peninsula using the Met Office Unified Model (MetUM)

Abstract: A foehn event on 27 January 2011 over the Larsen C Ice Shelf (LCIS), Antarctic Peninsula and its interaction with an exisiting ground-based cold-air pool is simulated using the MetUM atmospheric model at kilometre and sub-kilometre scale grid spacing. Atmospheric model simulations at kilometre grid scales are an important tool for understanding the detailed circulation and temperature structure over the LCIS, especially the occurrence of foehn-induced surface melting, erosion of cold-air pools, and low-level w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 126 publications
(211 reference statements)
0
30
0
Order By: Relevance
“…One of the rare observational studies of gap flow jets during foehn events at the Antarctic Peninsula is shown by [19] using aircraft data. A weak LLJ during a foehn event detected by radiosonde measurements over the Larsen Ice Shelf is shown by [20], while a strong LLJ with 15 m/s during a foehn situation over the Larsen Ice Shelf was measured by [21] using aircraft data.…”
Section: Introductionmentioning
confidence: 99%
“…One of the rare observational studies of gap flow jets during foehn events at the Antarctic Peninsula is shown by [19] using aircraft data. A weak LLJ during a foehn event detected by radiosonde measurements over the Larsen Ice Shelf is shown by [20], while a strong LLJ with 15 m/s during a foehn situation over the Larsen Ice Shelf was measured by [21] using aircraft data.…”
Section: Introductionmentioning
confidence: 99%
“…Step 1. Agree on a state-of-the-art DEM of the Antarctic continent, with a sufficiently high spatial resolution to be appropriate for even kilometre and sub-kilometre models (Orr et al, 2021). This could in our minds be REMA (Howat et al, 2019) at a 100 m grid resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Step 1: Agree on a state-of-the-art DEM of the Antarctic continent, with a sufficiently high spatial resolution to be appropriate for even kilometre and sub-kilometre models (Orr et al, 2021). This could in our minds be the Reference Elevation Model of Antarctica (REMA, Howat et al ( 2019)) at 100-metre grid resolution.…”
Section: Discussionmentioning
confidence: 99%